2011
DOI: 10.1590/s0104-11692011000500009
|View full text |Cite
|
Sign up to set email alerts
|

Workplace stress in nursing workers from an emergency hospital: Job Stress Scale analysis

Abstract: This study identifies workplace stress according to the Job Stress Scale and associates it with socio-demographic and occupational variables of nursing workers from an emergency hospital. This is a cross-sectional study and data were collected through a questionnaire applied to 388 nursing professionals. Descriptive statistics were applied; univariate and multivariate analyses were performed. The results indicate there is a significant association with being a nursing technician or auxiliary, working in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
3
21
1
5
Order By: Relevance
“…In this sense, the results of this study showed that to be a technician/auxiliary nurse, to have been in the job for 14 years or more and to have completed high school or an undergraduate degree are conditions that can lead to the development of stress, given that these workers were classified in the high-strain quadrant (p<0.05). These results corroborate those of another study (13) , performed in an emergency room of a hospital in the South of Brazil, in which it was found that to be a technician/auxiliary nurse, with more than 15 years in the job, and to have low social support cause a greater chance of having high deterioration.…”
Section: Despite the Divergence Of Results It Is Importantsupporting
confidence: 90%
See 1 more Smart Citation
“…In this sense, the results of this study showed that to be a technician/auxiliary nurse, to have been in the job for 14 years or more and to have completed high school or an undergraduate degree are conditions that can lead to the development of stress, given that these workers were classified in the high-strain quadrant (p<0.05). These results corroborate those of another study (13) , performed in an emergency room of a hospital in the South of Brazil, in which it was found that to be a technician/auxiliary nurse, with more than 15 years in the job, and to have low social support cause a greater chance of having high deterioration.…”
Section: Despite the Divergence Of Results It Is Importantsupporting
confidence: 90%
“…In Unlike another study (13) which indicated that workers who are only employed in the institution studied presented a greater percentage in the passive job followed by the low-strain (p=0.361) quadrants, in the present study, in addition to the prevalence in the high-strain quadrant, 185 (45.2%) of them were classified as having reduced work ability. One possible explanation for this result may be related to the fact that many workers are not limited to only working the weekly contracted hours.…”
Section: Furthermore the Deficit Of Employees That Manycontrasting
confidence: 50%
“…Among nursing assistants and technicians, the lower social support was significantly associated with a greater exposure to stress. It is assumed that their position of subordinated work in relation to other health professionals may favor difficult and conflicting interpersonal interactions (18) , as well as the low social support related to this occupational class.…”
Section: Discussionmentioning
confidence: 99%
“…In the first (14) , there was a prevalence in the passive job quadrant (29.9%), followed by active job (28.5%), and lower prevalence in high strain (21.2%). In the second study (18) , a higher prevalence of workers in passive jobs (35.6%) was found, followed by low strain (26.5%), and also higher prevalence of the quadrant high strain, around 21%.…”
Section: Resultsmentioning
confidence: 76%